Konseling Menyusui Berbasis Android terhadap Keberhasilan Asi Eksklusif di Masa Pandemi Covid-19 - Eni Folendra Rosa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study examines the effect of Android-based breastfeeding counseling during the COVID-19 pandemic and the success of exclusive breastfeeding. The research design used in this study was experimental with a controlled trial design. The results showed that exclusive breastfeeding was 2.06 times more in the intervention group (android-based breastfeeding counseling) than in the control group (RR=2.06; 95% CI). In conclusion, the proportion of exclusive breastfeeding to mothers who received Android-based breastfeeding counseling was more significant than that of mothers who did not receive Android-based counseling. Keywords: Android, exclusive breastfeeding, Breastfeeding Counseling